Comprehensive paediatric assessments for children in out of home care - Griffiths, Glenys (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness of comprehensive paediatric assessments in identifying physical, developmental, mental health, and behavioural needs, and in facilitating access to appropriate interventions compared with usual care (partial assessment) or no assessment for children entering out of home care.